2015
DOI: 10.1103/physrevb.91.081105
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfine coupling and spin polarization in the bulk of the topological insulatorBi2Se3

Abstract: Nuclear magnetic resonance (NMR) and transport measurements have been performed at high magnetic fields and low temperatures in a series of n-type Bi2Se3 crystals. In low density samples, a complete spin polarization of the electronic system is achieved, as observed from the saturation of the isotropic component of the 209 Bi NMR shift above a certain magnetic field. The corresponding spin splitting, defined in the phenomenological approach of a 3D electron gas with a large (spinorbit-induced) effective g-fact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
41
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 26 publications
8
41
0
2
Order By: Relevance
“…Unusually large 209 Bi linewidths have been noticed in previous works [14,[19][20][21], but indirect coupling was not invoked as a possible origin. Besides, rather fast 209 Bi NMR spin echo decays were observed, in particular in the central region of the spectra, but could not be explained.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unusually large 209 Bi linewidths have been noticed in previous works [14,[19][20][21], but indirect coupling was not invoked as a possible origin. Besides, rather fast 209 Bi NMR spin echo decays were observed, in particular in the central region of the spectra, but could not be explained.…”
Section: Discussionmentioning
confidence: 99%
“…In the supplement of Ref. [21], a single crystal 77 Se NMR spectrum consisting of one line with a field-independent ∼12 kHz linewidth is reported. This suggests the authors observed only Se out , while Se in was missing, probably due to noise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is accompanied by an increasing anisotropy of the Fermi surface observed as the Fermi level increases in the conduction band. More recent transport, 7-9 NMR, 9 and magneto-optics 10 measurements have confirmed the original parameters phenomenologically describing the bulk conduction band, and in some cases 10 connected them to the 3D Dirac Hamiltonian for massive fermions applied to topological insulators.…”
Section: Introductionmentioning
confidence: 91%
“…The only NMR studies of TI surface states published to date were done on nanocrystals (7) and nanowires (8), by inferring the TI properties in the limit of high surface-tovolume ratios. A recent study on Bi 2 Se 3 performed at high magnetic fields provides the means of approaching the quantum limit in TIs via NMR (9). Because films grown by molecular beam epitaxy (MBE) and cleaved surfaces from single crystals are universally studied by most researchers, NMR experiments that directly interrogate TI properties in a depth-resolved manner beneath the surface of epitaxial TI films would be preferred, as they would enable comparison with the literature.…”
Section: Significancementioning
confidence: 99%